Mehrskalige Charakterisierung der Hochtemperatur-Brennstoffzelle (SOFC) - Wankmüller, Florian (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2022)
The solid oxide fuel cell (SOFC) as electricity and heat producer of the future represents a key technology in the context of a climate-friendly energy supply. Research focuses on the improvement of the lifetime and cost reduction of the SOFC components. In this work, microstructural changes that occur during cell production and operation (aging process) are identified by multiscale examination methods.